2019
DOI: 10.1214/18-aop1320
|View full text |Cite
|
Sign up to set email alerts
|

Sampling perspectives on sparse exchangeable graphs

Abstract: Recent work has introduced sparse exchangeable graphs and the associated graphex framework, as a generalization of dense exchangeable graphs and the associated graphon framework. The development of this subject involves the interplay between the statistical modeling of network data, the theory of large graph limits, exchangeability, and network sampling. The purpose of the present paper is to clarify the relationships between these subjects by explaining each in terms of a certain natural sampling scheme assoc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(75 citation statements)
references
References 26 publications
0
75
0
Order By: Relevance
“…Here we are most interested in what [25] introduces as GP-convergence, where GP stands for graphex process. This notion is closely related to the notion of sampling convergence for graphs introduced in [4]; see Lemma 5.4 in that paper, as well as the discussion at the end of this section. Janson showed that the following are equivalent if W, W 1 , W 2 , .…”
Section: Definitions and Statements Of Main Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…Here we are most interested in what [25] introduces as GP-convergence, where GP stands for graphex process. This notion is closely related to the notion of sampling convergence for graphs introduced in [4]; see Lemma 5.4 in that paper, as well as the discussion at the end of this section. Janson showed that the following are equivalent if W, W 1 , W 2 , .…”
Section: Definitions and Statements Of Main Resultsmentioning
confidence: 86%
“…Remark 2.3. (1) Following [4], we defined a graphex process as a stochastic process taking values in a space of graphs with labels in R + . Alternatively, one might want to define a graphex process as a process taking values in the space of unlabeled graphs without isolated vertices.…”
Section: Definitions and Statements Of Main Resultsmentioning
confidence: 99%
See 3 more Smart Citations